2013
DOI: 10.1073/pnas.1301047110
|View full text |Cite
|
Sign up to set email alerts
|

Aneuploidy underlies a multicellular phenotypic switch

Abstract: Although microorganisms are traditionally used to investigate unicellular processes, the yeast Saccharomyces cerevisiae has the ability to form colonies with highly complex, multicellular structures. Colonies with the "fluffy" morphology have properties reminiscent of bacterial biofilms and are easily distinguished from the "smooth" colonies typically formed by laboratory strains. We have identified strains that are able to reversibly toggle between the fluffy and smooth colony-forming states. Using a combinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
106
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(115 citation statements)
references
References 49 publications
(56 reference statements)
8
106
1
Order By: Relevance
“…Other recent studies reveal that unisexual reproduction can generate phenotypic and genotypic diversity de novo, and that much of this diversity is attributable to aneuploidy (Ni et al 2013). Although a prevailing view is that aneuploidy is uniformly deleterious, in fungi, a large number of studies have revealed that aneuploidy promotes adaptive evolutionary trajectories and underlies morphogenic switches (Yona et al 2012;Tan et al 2013). Similar pathways may operate in animals as well, such as the frequent changes in ploidy and aneuploidy observed in hepatocytes (Duncan et al 2010).…”
Section: Monokaryotic Fruiting Resembles Hyphal Sexual Developmentmentioning
confidence: 99%
“…Other recent studies reveal that unisexual reproduction can generate phenotypic and genotypic diversity de novo, and that much of this diversity is attributable to aneuploidy (Ni et al 2013). Although a prevailing view is that aneuploidy is uniformly deleterious, in fungi, a large number of studies have revealed that aneuploidy promotes adaptive evolutionary trajectories and underlies morphogenic switches (Yona et al 2012;Tan et al 2013). Similar pathways may operate in animals as well, such as the frequent changes in ploidy and aneuploidy observed in hepatocytes (Duncan et al 2010).…”
Section: Monokaryotic Fruiting Resembles Hyphal Sexual Developmentmentioning
confidence: 99%
“…Recently it was suggested that in yeast, aneuploidy may be a "quick fix" to tolerate stress during adaptive evolution since an aneuploidy state was shown to be transient while more "refined" mutations take over the culture (Yona et al 2012). Moreover, changes in aneuploidy can be an "on-off switch" for colony morphological changes (Tan et al 2013).…”
mentioning
confidence: 99%
“…In addition, some of the colonies had scalloped edges, a property observed in some colonies derived from aneuploid strains (Jung et al 2011;Tan et al 2013). The possibility of aneuploidy is also suggested by the high frequency of nondisjunction observed for cXII ( Figure 1B).…”
Section: Gross Chromosomal Rearrangements and Ploidy Changes In The Gmentioning
confidence: 75%